2010
DOI: 10.1016/j.crohns.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a patient-support program on mesalamine adherence in patients with ulcerative colitis — A prospective study

Abstract: This nurse-delivered patient-support program did not significantly improve medication adherence or quality-of-life beyond standard care at short and medium-term time-points. Simply discussing and measuring adherence improved mesalamine adherence in both groups in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…The proportion of patients taking 5-ASA or Aza/MP who had a histological score >3.1 was also similar (33% and 42% respectively). Although we did not measure adherence to these medications directly, prior studies from our patient population have reported over 70% adherence rates 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of patients taking 5-ASA or Aza/MP who had a histological score >3.1 was also similar (33% and 42% respectively). Although we did not measure adherence to these medications directly, prior studies from our patient population have reported over 70% adherence rates 21 .…”
Section: Resultsmentioning
confidence: 99%
“…29 Simple interventions, such as telephone reminders and education, may not be sufficient motivators to correct intentional nonadherence behavior. 30,31 Self-evaluation of the benefits of medical therapy and motivational interviewing may be required to improve the priority of rectal mesalamine adherence in patients' daily lives. 28,30,32 There are a number of limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on blood-based peripheral biomarkers of endoscopic activity, but did not include validated stool-based markers, such as calprotectin. Finally, we did not measure medication adherence directly, but prior studies from our patient population have reported 70-80% of mesalamine prescriptions are refilled over 6 months (28). …”
Section: Discussionmentioning
confidence: 99%